The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1476-5381.1996.tb15193.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide, but not prostaglandins, in the vascular sympathoinhibitory effects of losartan in the pithed spontaneously hypertensive rat

Abstract: 1 The aim of this study was to investigate whether nitric oxide (NO) and/or vasodilator prostaglandins (PGs) are involved in the sympathoinhibitory effects exerted by losartan versus the vascular responses elicited by spinal cord electrical stimulation (SCS) in pithed spontaneously hypertensive rats (SHRs).2 SHRs were given orally and for 8 days either losartan (10 mg kg-' daily) or distilled water (controls).After pithing, blood pressure, heart rate, cardiac output, renal and muscular blood flows (pulsed Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…These measures make the HR data more difficult to interpret. However, like in other studies [12,24], no effect of AT 1 -blockade on the increase in HR was observed. The facilitatory effect of Ang II, therefore, concerns the vasculature and not the heart, under our experimental conditions.…”
Section: Stimulation Experimentssupporting
confidence: 74%
See 1 more Smart Citation
“…These measures make the HR data more difficult to interpret. However, like in other studies [12,24], no effect of AT 1 -blockade on the increase in HR was observed. The facilitatory effect of Ang II, therefore, concerns the vasculature and not the heart, under our experimental conditions.…”
Section: Stimulation Experimentssupporting
confidence: 74%
“…In several studies, both in normotensive and hypertensive animals, an inhibitory effect of ACE inhibition or AT 1 ‐blockade on α‐adrenergic responses at the level of the vascular smooth muscle cell has been described [6,10,14,25]. In other studies, AT 1 ‐blockade was shown not to influence α‐adrenergic responses in the pithed SHR [13,24]. The rise in DBP caused by exogenous NA was significantly greater in SHR than in WKY.…”
Section: Noradrenaline Experimentsmentioning
confidence: 99%